Comparative analysis of food and beverage companies financial performance on the Indonesia stock exchange - Eugenia, Felicia; Khairudin, Khairudin (Institute of Computer Science (IOCS), 2025)
Performance measurement can be utilized to oversee the company’s operations. Financial performance is conducted to assess the regulations that have been implemented in the company’s financial activities. The objective of this research is to assess the financial performance of the Food and Beverage companies recorded on the IDX from 2018 to 2020 by utilizing profitability ratios as measurement tools. This research employs a descriptive research design along with comparative analysis methods, relying on secondary data. The author observes that the financial performance of the six Food and Beverage companies is below par (low) as they fail to reach the industry standard average thresholds of 30% for Return on Assets (ROA), 40% of Return on Equity (ROE), and 20% of Net Profit Margin (NPM). Only three out of six companies achieved the industry standard average of Gross Profit Margin (GPM) threshold (30%), namely PT Campina Ice Cream Industry Tbk, PT Nippon Indosari Corpindo Tbk, and PT Ultrajaya Milk Industry Tbk.